The Practice of Marketing Public Relations In Multinational Companies in Indonesia - Lina Sinatra Wijaya (Petra International Journal of Business Studies, 2019)
The growth of public relations and its acceptance as a valuable, sometimes essential, marketing practice is practically universal . This study aims to find out the marketing communication models applied in Multinational companies in Indonesia. The study provides an analysis of the role of marketing public relations in Multinational companies and this study also explores the role of marketing public relations in the multinational or global companies in Indonesia, to establish whether it is considered to be an important function for a multinational company. The data was gathered through in-depth interview and telephone interview technique involving six multinational companies in Indonesia. The result of this study shows that Marketing public relations officers in multinational companies in Indonesia do apply a mixed model of communications in their operations. This mixed model is a mixture of the press agentry and a two-way asymmetrical model. These two models seem to be the models which are applied in most multinational companies in Indonesia, even though they still use external agencies (consultancies) for handling certain issues.